Multiculturalism in Twenty-First Century Britain - Toufouti , Youcef (Journal of Human Sciences, 2021)
In 2012, the opening ceremony of the London Olympic Games projected an image of a New Britain: multicultural, liberal, and a well-meaning country. Astonishingly, after the Brexit referendum of 2016, it seemed as a system of multicultural values about what Britain was like had been overturned. Hence, this article examines the notion of multiculturalism in relation to other concepts such as immigration, Britishness, terrorism, and Brexit. Further, the article attempts to explore whether multiculturalism is a divisive factor that leads to disunity through promoting cultural differences or it is a driving force for unity that leads to more integration of ethnic minorities and a fairer British society.